2022
DOI: 10.1038/s41598-022-13984-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural networks for automated scoring of pentagon copying test results

Abstract: This study aims to investigate the accuracy of a fine-tuned deep convolutional neural network (CNN) for evaluating responses to the pentagon copying test (PCT). To develop a CNN that could classify PCT images, we fine-tuned and compared the pre-trained CNNs (GoogLeNet, VGG-16, ResNet-50, Inception-v3). To collate our training dataset, we collected 1006 correct PCT images and 758 incorrect PCT images drawn on a test sheet by dementia suspected patients at the Osaka City Kosaiin Hospital between April 2009 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Maruta et al reported that the sensitivity of PCT was low at 29.4%; however, when pre-trained artifical intelligence (AI) models (fine-tuned GoogLeNet CNN) were used to distinguish the difference between pentagons drawn by dementia patients and those drawn by non-dementia patients, AI was able to improve both the sensitivity and specificity with a high level of accuracy, namely approximately 79 to 93% ( 12 ). Administering PCT and CCT to patients with Parkinson's disease dementia, Alty JE reported that the sensitivity of PCT was 26% and CCT was 74%, showing that CCT was superior to PCT in sensitivity ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maruta et al reported that the sensitivity of PCT was low at 29.4%; however, when pre-trained artifical intelligence (AI) models (fine-tuned GoogLeNet CNN) were used to distinguish the difference between pentagons drawn by dementia patients and those drawn by non-dementia patients, AI was able to improve both the sensitivity and specificity with a high level of accuracy, namely approximately 79 to 93% ( 12 ). Administering PCT and CCT to patients with Parkinson's disease dementia, Alty JE reported that the sensitivity of PCT was 26% and CCT was 74%, showing that CCT was superior to PCT in sensitivity ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Automated scoring methods that utilize machine learning methods offer the potential to address some or all of these weaknesses. For example, deep-learning techniques have demonstrated promising performance in automating ratings for the PDT 7,8 , Rey Complex Figure Test 9,10 , and Clock Drawing Test 11,12 . However, the primary objective of the previous automated scoring is to reproduce human-based conventional ratings and few machine learning approaches directly predict cognitive performance from drawings 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Automated scoring methods that utilize machine learning methods offer the potential to address some or all of these weaknesses. For example, deep-learning techniques have demonstrated promising performance in automating ratings for the PDT 7 , 8 , Rey Complex Figure Test 9 , 10 , and Clock Drawing Test 11 , 12 . However, the primary objective of the previous automated scoring is to reproduce human-based conventional ratings, and few machine learning approaches directly predict cognitive performance from drawings 13 .…”
Section: Introductionmentioning
confidence: 99%